Дело страстей. Рец. на кн.: Велижев М. Чаадаевское дело: Идеология, риторика и государственная власть в николаевской России. М.: Новое литературное обозрение, 2022 [L’affaire des passions. Review of _Chaadaevskoe delo: Ideologiia, ritorika i gosudarstvennaia vlast’ v nikolaevskoi Rossii_, by Mikhail Velizhev] - Liamina, Ekaterina (Slavica Revalensia, 2023)
This is a review of the recently published book on the Chaadaev affair—the culmination of Mikhail Velizhev’s research, which took him over twenty years to complete.